2013
DOI: 10.1371/journal.pone.0072551
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gender Differences in Genetic Risk: Association of TNFAIP3 Polymorphism with Male Childhood-Onset Systemic Lupus Erythematosus in the Japanese Population

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a systemic multisystem autoimmune disorder influenced by genetic background and environmental factors. Our aim here was to replicate findings of associations between 7 of the implicated single nucleotide polymorphisms (SNPs) in IRF5, BLK, STAT4, TNFAIP3, SPP1, TNIP1 and ETS1 genes with susceptibility to childhood-onset SLE in the Japanese population. In particular, we focused on gender differences in allelic frequencies.Methodology/Principal FindingsThe 7 SNPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Among these, 13 did not study the association of TNFAIP3 gene polymorphisms with SLE, 1 article for data duplication (31). Thus, 20 articles met our inclusion criteria (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Among the eligible articles, two articles (22,24) contained data on two or more different groups, and these groups were analyzed independently.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 13 did not study the association of TNFAIP3 gene polymorphisms with SLE, 1 article for data duplication (31). Thus, 20 articles met our inclusion criteria (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Among the eligible articles, two articles (22,24) contained data on two or more different groups, and these groups were analyzed independently.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Among the eligible articles, two articles (22,24) contained data on two or more different groups, and these groups were analyzed independently. Finally, a total of 23 studies in 20 articles including 18,501 patients with SLE and 30,435 healthy controls were considered in our meta-analysis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). There were 20 studies on rs2230926 (12-27, 30), 10 studies on rs5029939 (11,13,17,22,23,26,(28)(29)(30), 8 studies on rs3757173 (16,17,22,27,30), 5 studies on rs5029937 (20,22,26,30).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of clinical characteristics indicated that men younger than 33 at the time of diagnosis were more likely to develop lupus nephritis, and that patients of Asian descent tend to have more severe disease, including the renal manifestations. [15] The patient was diagnosed with SLE based on the classification of the American College of Rheumatology. The serology examination of SLE shows high titre of ANA and Anti-dsDNA.…”
Section: Discussionmentioning
confidence: 99%